2017
DOI: 10.7243/2054-992x-4-3
|View full text |Cite
|
Sign up to set email alerts
|

The intellectual profiles of high functioning elderly persons with an autism spectrum disorder

Abstract: Research into the cognitive profiles of older adults with ASD is limited. We know little about how aging affects individuals with ASD and how this influences their needs. The present study is the first to examine intelligence profiles in older adults with ASD. WAIS-III performance of 23 elderly with ASD and 23 neurotypical older persons was examined. The two groups were matched on age and level of education. Results showed highly similar intelligence profiles, with the exception of processing speed index, on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 21 publications
1
6
2
Order By: Relevance
“…However, at the same time, they also had significantly lower scores on the processing speed index compared to the controls. This finding is in keeping with results reported by Spek et al (2017) who also found that older adults with Autism performed significantly worse than TD older adults on processing speed measures. Impairment in processing speed has also been found in previous studies with children and adults with Autism (Geurts et al 2008; Powell et al 2017; Spek et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, at the same time, they also had significantly lower scores on the processing speed index compared to the controls. This finding is in keeping with results reported by Spek et al (2017) who also found that older adults with Autism performed significantly worse than TD older adults on processing speed measures. Impairment in processing speed has also been found in previous studies with children and adults with Autism (Geurts et al 2008; Powell et al 2017; Spek et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In the light of conflicting findings from previous research, this study aimed to address the following questions:Are there significant differences between people aged over 50 with and without Autism on indices of the WAIS-IV? It is hypothesised that similar to younger people with Autism and results from Spek et al’s (2017) study, older adults with Autism will have lower scores in processing speed and working memory indices relative to TD controls.Are there significant differences between people aged over 50 with and without Autism in WMS-IV memory indices when: (a) memory index scores are adjusted for IQ and (b) memory index scores are not adjusted for IQ?…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations